From Naija to Chitown: The New African Diaspora and digital representations of place. (September 2015) - Heyd, Theresa; Honkanen, Mirka
Abstract: In the past two decades, the New African Diaspora (NAD) has emerged as a globally mobile community that epitomizes life under super-diverse conditions. Coming from countries of origin in sub-Saharan Africa, its members form a network with an increasing global significance, with the largest hubs in the US and the UK. Despite or because of the high mobility of its representatives, their discourses about place, and in particular specific urban spaces, are charged with social and symbolic meaning. NAD members show strong and overt stances toward the cities they are affiliated with, so that localities become anchors for displaying sociolinguistic identity. This tendency is especially pronounced and on-record in the digital diaspora, i.e. in online discourse produced in diasporic web forums or on social media. Early sociolinguistic approaches to computer-mediated communication (CMC) had largely disregarded the notions of geographic place and locally anchored identity by focusing on the concept of anonymous users in an abstract, dislocated cyberspace. However, through the rise of social media and mobile devices, the notion of place and (urban) space is emerging in the analysis of digital discourse. This study builds on this growing tendency by exploring linguistic representations of urban space in the digital NAD. The approach is based on a large-scale corpus representing the Nigerian digital diaspora, downloaded from the online discussion forum nairaland.com. In this resource, the social meaning of urban space and its representations are explored both in terms of linguistic encoding strategies and with regard to emerging themes. Corpus-based text analysis is used to detect linguistic patterns of symbolic de/valoring of specific places (e.g. proximal deictic anchoring through here in x constructions, as well as the use of affectionate place names such as Naija or Chitown ). In addition, qualitative close-reading of the material reveals emerging themes that represent recurring stances toward place within the community. In sum, our study provides a thorough and methodologically varied overview of sociolinguistic representations of place in a globally mobile community of practice, and in particular of the importance of place concepts in digital diasporas. It thus contributes to a better understanding of the sociolinguistics of CMC and its emerging focus on place and space. Highlights: We analyze place concepts in a diasporic online community. Place is made meaningful through strategies such as deictic anchoring and nonstandard toponyms. Geolocation plays a substantial role in discursive practices of online communities.